Shift work and sick leave - Kleiven, M.; Bøggild, Henrik; Jeppesen, Hans Jeppe (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVE ': 'Shift workers working nights are known to have higher morbidity from certain illnesses than day workers. This study examined episodes of certified sick leaves of day workers and shift workers in a large industrial plant to examine whether slowly rotating shift work leads to increased risk of sick leave.' ' METHODS ': 'In a case-base design more than 11 000 episodes of sick leave, lasting more than 3 days, were obtained from the sick-leave files of a chemical plant in Norway. The diagnoses were grouped into 5 categories according to information on their work schedules. The workers included in the study were divided into 3 groups. They worked slowly rotating 3 shifts, 2 shifts without night work, and daytime schedules. Results For all the diagnoses the shift workers and day workers were evenly distributed among the cases and the referents, the odds ratios ranging from 0.8 to 1.2. The risk of sick leave did not change with the number of years in shift work. There was a higher risk of sick leave with musculoskeletal diagnoses among the 2-shift workers.' ' CONCLUSION ': 'In this study shift workers did not have a higher risk of sick leave for diseases that, in previous studies, have been shown to be related to shift and night work. Although bias may be present in the study, the results are in line with those of previous studies, and they suggest that even certified sick leaves are not a valid proxy for morbidity.
Keywords: cardiovascular disease; case-referent study; gastrointestinal disease; morbidity; night work